Dynamics of scientific publications on the MERS-CoV outbreaks in Saudi Arabia - Ali A. Rabaan; Shamsah H. Al-Ahmed; Ali M. Bazzi; Jaffar A. Al-Tawfiq (Elsevier, 2017)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is an emerging disease with a relatively high case fatality rate. Most cases have been reported from Saudi Arabia, and the disease epidemic potential is considered to be limited. However, human-human transmission has occurred, usually in the context of healthcare facility-associated outbreaks. The scientific and medical community depends on timely publication of epidemiological information on emerging diseases during outbreaks to appropriately target public health responses. In this review, we considered the academic response to four MERS CoV outbreaks that occurred in Al-Hasa in 2013, Jeddah in 2014 and Riyadh in 2014 and 2015. We analysed 68 relevant epidemiology articles. For articles for which submission dates were available, six articles were submitted during the course of an outbreak. One article was published within a month of the Al-Hasa outbreak, and one each was accepted during the Jeddah and Riyadh outbreaks. MERS-CoV epidemiology articles were cited more frequently than articles on other subjects in the same journal issues. Thus, most epidemiology articles on MERS-CoV were published with no preferential advantage over other articles. Collaboration of the research community and the scientific publishing industry is needed to facilitate timely publication of emerging infectious diseases. Keywords: Middle East Respiratory Syndrome Coronavirus, Outbreak, Epidemiology, Publication, Saudi Arabia, MERS-CoV